Formation of foreign language communicative competence of future lawyers - Balanaieva, Oksana; Mamonova, Olena; Khuda, Nataliia; Hupka-Makohin, Nadiya; Morozovska, Liudmyla (Revista Eduweb, 2023)
This paper focuses on the development of foreign language communicative competence of students studying law. The research used different methods to study how students studying law can improve their ability to communicate in a foreign language. There was looked at existing research and did a survey to understand more about how students can improve their language skills. The results of the study reveal the main directions of scientific developments on issues related to the formation of foreign language communicative competence of students of law specialties. The priority of development, assessment of components, and the procedure of this process from a practical point of view have been clarified. The paper emphasizes the importance of foreign language communicative competence in the field of law and highlights the challenges that students face in acquiring these skills.